2022
DOI: 10.1037/xge0001144
|View full text |Cite
|
Sign up to set email alerts
|

Personal relative deprivation and the belief that economic success is zero-sum.

Abstract: Why do people view economic success as zero-sum? In seven studies (including a large, nationally representative sample of more than 90,000 respondents from 60 countries), we explore how personal relative deprivation influences zero-sum thinking-the belief that one person's gains can only be obtained at other people's expense. We find that personal relative deprivation fosters a belief that economic success is zero-sum, and that this is true regardless of participants' household income, political ideology, or s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 86 publications
1
18
0
Order By: Relevance
“…Consequently, these beliefs increased participants’ interest in dominance. Just as economic downturns (Sirola & Pitesa, 2017) and upward comparisons (Ongis & Davidai, 2021) foster zero-sum beliefs, any impending loss may foster such beliefs and therefore lead people to engage in more dominant behaviors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Consequently, these beliefs increased participants’ interest in dominance. Just as economic downturns (Sirola & Pitesa, 2017) and upward comparisons (Ongis & Davidai, 2021) foster zero-sum beliefs, any impending loss may foster such beliefs and therefore lead people to engage in more dominant behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…People often view tangible and intangible resources as zero-sum, perceiving one’s gains as inevitably coming at others’ expense (Johnson et al, 2022; Meegan, 2010). For example, people believe that wealthy individuals become rich at the expense of worse-off others (Davidai & Ongis, 2019; Ongis & Davidai, 2021; Różycka-Tran et al, 2015; Sirola & Pitesa, 2017), that minority group members advance at the expense of the majority group (Bobo & Hutchings, 1996; Brown & Jacoby-Senghor, 2021; Esses et al, 1998; Kimmel, 2013; Norton & Sommers, 2011; Smithson et al, 2015), and that other countries and political parties gain at their own country’s and party’s expense (Andrews Fearon et al, 2021; Boyer & Petersen, 2017; Johnson, 2018; Roberts & Davidai, 2021).…”
Section: Zero-sum Beliefs About Social Hierarchiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it has been shown that such specific zero-sum beliefs (e.g., about gender relations) are malleable, context dependent, and do not necessarily reflect a generalized mindset (e.g., about intergroup relations; Wilkins et al, 2015). For instance, zero-sum beliefs are influenced by perceptions of the economy (Sirola & Pitesa, 2017) and the status-quo (Davidai & Ongis, 2019), mental models of causality (Smithson & Shou, 2016), organizational procedures (Andrews Fearon & Davidai, 2021), and experiences of symbolic threat (Smithson et al, 2015) and personal relative deprivation (Ongis & Davidai, in press). Thus, although a generalized mindset indicates a readiness to view social relations as zero-sum, contextual factors clearly play an important role in determining whether people exhibit these beliefs within any given situation.…”
Section: The Psychology Of Zero-sum Beliefsmentioning
confidence: 99%
“…Even though life entails many such opportunities for joint gains, people often fail to see them as such, viewing success as a zero-sum game where one’s gains are inevitably offset by others’ losses (Foster, 1965; Johnson et al, 2021; Ongis & Davidai, 2021; Roberts & Davidai, 2021; Różycka-Tran et al, 2015). Such zero-sum beliefs are associated with many adverse personal and societal consequences.…”
mentioning
confidence: 99%